Detonation Parameters of PlSEM Plastic Explosive - Cardoso Anastácio, Aline; Šelešovský, Jakub; Künzel, Martin; Kučera, Jindřich; Pachman, Jiří (The Publishing of Łukasiewicz – Institute of Industrial Organic Chemistry, 2019)
PlSEM is a plastic explosive based on RDX, PETN and non-explosive binder used in linear shaped charges for demolition purposes. Experimentally obtained detonation parameters are presented in this contribution. The detonation velocity was measured for cylindrical charges of various diameters, with and without confinement. The detonation pressure and particle velocity were determined using impedance window matching technique, and cylinder tests were used to obtain parameters of the JWL equation of state of the detonation products. The detonation velocity from 7.75 to 8.05 km·s -1 were obtained for unconfined charges with diameters from 4 mm to 8 mm, and from 8.15 to 8.24 km·s-1 for charges with 25 mm diameter. The experimentally determined detonation pressure was found to be 24.6 GPa.
Detonační parametry plastické trhaviny PlSEM
Keywords: detonation velocity; PlSEM; plastic explosive; detonation pressure; cylinder test; detonační rychlost; PlSEM; plastická trhavina; detonační tlak; cylindr test